PENDUGAAN PENGELUARAN PER KAPITA DESA DI KABUPATEN JEMBER DENGAN METODE PREDIKSI TAK BIAS LINIER TERBAIK EMPIRIS - Dariani Matualage (FMIPA Universitas Papua, 2014)
Per capita expenditure is very important for a region, It’s estimation are only conducted at national to district level based on National Socio-Economic Survey (Susenas) data conducted by BPS. The survey was designed for a national scale, so the estimation would have low precision if used for smaller sub-populations, such as villages. One attempt to improve the precision of the estimation is by increasing the effectiveness of the sample size known as the small area estimate (SAE). One method in SAE that is very well used for continuous data is the Empirical Best Linear Unbiased Prediction (EBLUP). EBLUP method is used to estimate per capita expenditure of each village in Jember District by using companion variables, the percentage of the Askeskin recipients in the last year. The result is that the estimation of village per capita expenditure in Jember Regency by EBLUP method have better precision than direct estimation. There are three outlier data including Karangrejo, Jember Lor and Sumbersari that have very high per capita expenditures because they are located in urban areas